2021
DOI: 10.3390/s21217019
|View full text |Cite
|
Sign up to set email alerts
|

Pultruded FRP Beams with Embedded Fibre Bragg Grating Optical Sensors for Strain Measurement and Failure Detection

Abstract: Composites have added new dimensions to the design and construction of buildings and structures. One of the wider spread composite applications in the construction industry is composite beams or pillars, which can be manufactured through pultrusion processes. These types of construction elements are usually used to withstand the weight of large loads, so their integrity must be guaranteed. Due to optical sensors’ advantages over their electrical counterparts—small sizes, low weight, non-conductive, and immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Currently, composite materials can be obtained through a wide range of products, such as metals, ceramics, or even polymers. However, most applications of embedded FOSs focus on polymer matrix composites [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. In the composite production phase, FOSs can be embedded in the matrix or between the laminates of the composite to monitor certain conditions, such as the composite-stacking sequence, the resin flow during processing [ 62 ], the curing process of the laminates [ 71 ], or the misalignment of the fibres, which can lead to a significant reduction in the mechanical strength of the laminates [ 66 ].…”
Section: Embedded Sensors and Its Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, composite materials can be obtained through a wide range of products, such as metals, ceramics, or even polymers. However, most applications of embedded FOSs focus on polymer matrix composites [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. In the composite production phase, FOSs can be embedded in the matrix or between the laminates of the composite to monitor certain conditions, such as the composite-stacking sequence, the resin flow during processing [ 62 ], the curing process of the laminates [ 71 ], or the misalignment of the fibres, which can lead to a significant reduction in the mechanical strength of the laminates [ 66 ].…”
Section: Embedded Sensors and Its Applicationsmentioning
confidence: 99%
“…Therefore, the signal reduction obtained is not very significant when compared to the typical strain sensitivity of FBG sensors, which corresponds, for example, to 1.2 pm/με for the wavelength of 1550 nm, leading to the conclusion that incorporating FOSs is feasible and may be an alternative to conventional NDTs. Embedded optical fibre FBG sensors can also detect small delamination or disengagements between the matrix and fibres via an FBG spectrum change, allowing for the prediction of a fibre-reinforced polymer beam’s structural failure [ 69 ].…”
Section: Embedded Sensors and Its Applicationsmentioning
confidence: 99%
“…Currently, composite materials can be obtained through a wide range of products, such as metals, ceramics or even polymers. However, most applications of embedded FOSs focus on polymer matrix composites [65][66][67][68][69][70][71][72] [73] [74]. In the composite production phase, FOSs can be embedded in the matrix or between the laminates of the composite to monitor certain conditions, such as the composite stacking sequence, the resin flow during processing [65], the curing process of the laminates [73] or the misalignment of the fibres, which can lead to a significant reduction in the mechanical strength of the laminates [69].…”
Section: Applications For Composite Componentsmentioning
confidence: 99%
“…Therefore, the signal reduction obtained is not very significant when compared to the typical strain sensitivity of FBG sensors, which corresponds, for example, to 1.2 pm/με for the wavelength of 1550 nm, leading to the conclusion that incorporating FOSs is feasible and may be an alternative to conventional NDTs. Embedded optical fibre FBG sensors can also detect small delamination or disengagement between matrix and fibres via FBG spectrum change, allowing to predict a fibre-reinforced polymer beam structure failure [72].…”
Section: Applications For Composite Componentsmentioning
confidence: 99%
“…Among FRP production technologies, pultrusion [ 7 ] is a consecutive process aimed to produce FRP longitudinal elements with constant cross-sections, by means of using continuous roving soaked with resin ad heated to cure them. Regarding the type of pultruded FRP elements, Alhawamdeh et al [ 8 ] reported the I-shape profiles were the most used ones.…”
Section: Introductionmentioning
confidence: 99%